E-Mail Notification of Postal Delivery Universiti Utara Malaysia - Faiq, Hosam I. (2008)
With E-mail notification for postal delivery UUM services can be obtained easily way and flexibility to access the post info at any time in any location. This research introduces a prototype "E-mail notification for postal delivery UUM" that provides the students with the service of the post notification to them UUM Emails in order to reduce the time and the effort for the students. By using this prototype, students can easily get necessary information them post info by using the tracking umber that provide by the officer to obtain to the student for checking. So, they can save their time and effort by check them post online.